2023
DOI: 10.3390/foods12081640
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antibacterial Components and Modes in the Methanol-Phase Extract from a Herbal Plant Potentilla kleiniana Wight et Arn

Abstract: The increase in bacterial resistance and the decline in the effectiveness of antimicrobial agents are challenging issues for the control of infectious diseases. Traditional Chinese herbal plants are potential sources of new or alternative medicine. Here, we identified antimicrobial components and action modes of the methanol-phase extract from an edible herb Potentilla kleiniana Wight et Arn, which had a 68.18% inhibition rate against 22 species of common pathogenic bacteria. The extract was purified using pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Based on our recent studies [ 11 , 12 , 13 , 14 ], the M–CE method was employed to extract antibacterial substances from the fruit of A. villosum Lour. Its water loss rate was 73.68% after freeze-drying at −80 °C for 48 h. The extraction yields of the MPE and chloroform-phase extract (CPE) of A. villosum Lour.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on our recent studies [ 11 , 12 , 13 , 14 ], the M–CE method was employed to extract antibacterial substances from the fruit of A. villosum Lour. Its water loss rate was 73.68% after freeze-drying at −80 °C for 48 h. The extraction yields of the MPE and chloroform-phase extract (CPE) of A. villosum Lour.…”
Section: Resultsmentioning
confidence: 99%
“…The bacterial strains and media used in this study are shown in Table S7 . The incubation conditions of the bacterial strains were the same as those described in our recent reports [ 11 , 12 , 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations